HUBUNGAN TINGKAT KEBUGARAN FISIK DENGAN TINGKAT STRES PADA MAHASISWI PENGHAFAL AL-QURAN DI PONDOK PESANTREN KOTA MALANG: HUBUNGAN TINGKAT KEBUGARAN FISIK DENGAN TINGKAT STRES PADA MAHASISWI PENGHAFAL AL-QURAN DI PONDOK PESANTREN KOTA MALANG - Latifah Zulfa Rahmawati; Ali Multazam; Nurul Aini Rahmawati (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Stress is a condition that can occur in every individual, including female students who memorize the Quran. Students who memorize the Quran have activities that require them to concentrate highly, where these activities have the potential to cause stress. Exercise can reduce the impact of stress due to an increase in endorphin hormones. In addition, regular exercise can improve physical fitness. Therefore, female students who memorize the Quran must have a good level of physical fitness so that their activities are maximally fulfilled. This research aims to determine the relationship between physical fitness level and stress level in female students who memorize the Quran in Malang City. Method: using quantitative analytical observational with cross-sectional study design. The measuring instrument used was YMCA Step Test for physical fitness and PSS-10 (Perceived Stress Scale) for stress with a total of 30 female students memorizing the Quran. Results: the results of Fisher's Exact test obtained p value = 1.000 > 0.05. Conclusion: there is no relationship between physical fitness level and stress level in Al-Quran memorizers in Malang city.